استراتيجيات تنمية موقف الوسطية الدينية للأطفال المبكرين على نظر الإمام الغزالي - Hikmah, Nurul; Utami, Ary (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
The right time to cultivate an attitude of religious moderation is at an early age. It is at this early age that children must be given positive things so that later they can make habituation of noble character in their daily lives. Imam Ghozali is one of the scientists who is proficient in all fields of science and he has contributed greatly to the Islamic world. The purpose of this study is 1. What strategies can be used by educators to foster an attitude of religious moderation in early childhood? 2. How is the concept of fostering religious moderation according to Imam Ghozali in early childhood? This research method uses qualitative research using this type of research (library research). The results of this study are 1. The right strategy so that moderation can grow and become a good character attached to the child's personality is to pay attention to the characteristics of early childhood including a) Unique, b) Selfish, c) Active and energetic, d) Curiosity strong and enthusiastic, e) exploratory and adventurous, f) spontaneous, g) happy and rich in fantasy, h) still easily frustrated, i) short attention span, j) eager to learn and learn a lot from experience, k) Show more interest in friends. 2. To instill religious moderation in early childhood according to Imam Ghozali, focusing on awareness of loving people such as loving yourself can be done through formal educational institutions, family and habituation in daily life by prioritizing the values ​​of compassion (arrahmaniyah), fair (al-adl) and not excessive (at tawassuth).